Management of Nephrolithiasis in Pregnancy: Multi-Disciplinary Guidelines From an Academic Medical Center - Lee, Matthew S.; Fenstermaker, Michael A.; Naoum, Emily E.; Chong, Suzanne; Van de Ven, Cosmas J.; Bauer, Melissa E.; Kountanis, Joanna A.; Ellis, James H.; Shields, James; Ambani, Sapan; Krambeck, Amy E.; Roberts, William W.; et al. (Frontiers in Surgery, 2021)
Introduction The management of nephrolithiasis during pregnancy can be stressful for urologists due to concerns for investigations and treatments that may pose risk of fetal harm, and unfamiliarity with optimal management of these complex patients. In response, we created multi-disciplinary evidence-based guidelines to standardize the care for obstetric patients presenting with flank pain and suspicion for nephrolithiasis. Methods A multi-disciplinary team involving Urology, Obstetric Anesthesiology, Obstetrics and Gynecology, Diagnostic Radiology, and Interventional Radiology from a single academic medical center was assembled. A PubMed search was performed using keywords of pregnancy/antepartum, nephrolithiasis/calculi/kidney stones, ureteroscopy, non-obstetric surgery, complications, preterm delivery, MRI, computerized tomography, renal bladder ultrasound (RBUS), and anesthesia to identify relevant articles. Team members reviewed their respective areas to create a comprehensive set of guidelines. One invited external expert reviewed the guidelines for validation purposes. Results A total of 54 articles were reviewed for evidence synthesis. Four guideline statements were constructed to guide diagnosis and imaging, and seven statements to guide intervention. Guidelines were then used to create a diagnostic and intervention flowchart for ease of use. In summary, RBUS should be the initial diagnostic study. If diagnostic uncertainty still exists, a non-contrast CT scan should be obtained. For obstetric patients presenting with a septic obstructing stone, urgent decompression should be achieved. We recommend ureteral stent placement as the preferred intervention if local factors allow. Conclusions We present a standardized care pathway for the management of nephrolithiasis during pregnancy. Our aim is to standardize and simplify the clinical management of these complex scenarios for urologists.